2010
DOI: 10.1073/pnas.1007186107
|View full text |Cite
|
Sign up to set email alerts
|

Chronic lymphocytic leukemia modeled in mouse by targeted miR-29 expression

Abstract: B-cell chronic lymphocytic leukemia (B-CLL), the most common leukemia in the Western world, occurs in two forms, aggressive (showing for the most part high ZAP-70 expression and unmutated IgH V H ) and indolent (showing low ZAP-70 expression and mutated IgH V H ). We found that miR-29a is up-regulated in indolent human B-CLL as compared with aggressive B-CLL and normal CD19 + B cells. To study the role of miR-29 in B-CLL, we generated Eμ-miR-29 transgenic mice overexpressing miR-29 in mouse B cells. Flow cytom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
137
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(147 citation statements)
references
References 34 publications
9
137
1
Order By: Relevance
“…In aggressive B-CLL, however, miR-29b may directly target several important oncogenes. Consistent with the findings in other types of cancer, miR-29b probably shows a tumor suppressive function in B cell (Santanam et al, 2010;Kincaid et al, 2012;Liston et al, 2012). Thus, miR-29b can protect normal cells by regulating tumor immunosurveillance.…”
Section: Protecting Normal Cell By Regulating the Adaptive Immune Systemsupporting
confidence: 86%
“…In aggressive B-CLL, however, miR-29b may directly target several important oncogenes. Consistent with the findings in other types of cancer, miR-29b probably shows a tumor suppressive function in B cell (Santanam et al, 2010;Kincaid et al, 2012;Liston et al, 2012). Thus, miR-29b can protect normal cells by regulating tumor immunosurveillance.…”
Section: Protecting Normal Cell By Regulating the Adaptive Immune Systemsupporting
confidence: 86%
“…5). We recently reported significantly higher miR-29a and miR-29b expression levels in indolent CLL compared with normal CD19 + B cells (17). To study the role of miR-29 in CLL, we generated Eμ-miR-29 transgenic mice overexpressing miR-29 in B cells, and found that these mice developed a disease similar to indolent CLL (17).…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported significantly higher miR-29a and miR-29b expression levels in indolent CLL compared with normal CD19 + B cells (17). To study the role of miR-29 in CLL, we generated Eμ-miR-29 transgenic mice overexpressing miR-29 in B cells, and found that these mice developed a disease similar to indolent CLL (17). Given that DNMT3A is a known miR-29 target (16), we analyzed its expression in Eμ-miR-29 transgenics, and found down-regulated Dnmt3A expression in Eμ-miR-29 transgenic mice (17).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, an MDV mutant lacking the viral miR-155 analog grows normally in culture, yet is no longer capable of causing lymphomas in experimentally infected chickens (15). Similarly, miR-29 overexpression is causatively linked to CLL in humans and mice (4), and BLV causes B-cell tumors that closely resemble CLL (5). By analogy to MDV and miR-155, it would certainly be very interesting to see if a BLV mutant lacking miR-B4 loses the ability to induce B-cell tumors in infected ruminants.…”
mentioning
confidence: 99%
“…Moreover, one of the BLV miRNAs, miR-B4, shares the same seed sequence as cellular miR-29 and therefore can down-regulate many of the same mRNA targets. As miR-29 overexpression can induce chronic lymphocytic leukemia (CLL) in transgenic mice (4), and BLV induces CLL-like B-cell neoplasms in infected cattle and sheep (5), it appears likely that these viral miRNAs play an important role in BLV pathogenesis.…”
mentioning
confidence: 99%